Defective Ag–In–S/ZnS quantum dots: an oxygen-derived free radical scavenger for mitigating macrophage inflammation. Issue 43 (13th October 2021) - Gao, Na; Jing, Jing; Zhao, Hengzhi; Liu, Yazhou; Yang, Chunlei; Gao, Mengxu; Chen, Bingkun; Zhang, Rubo; Zhang, Xiaoling
Abstract : The as-prepared defective AIS/ZnS QDs have favorable oxygen-derived free radical scavenging abilities in vitro and exhibit benign anti-inflammatory activities in the model of lipopolysaccharide (LPS)-induced inflammation in macrophages. Abstract : Oxidative stress plays an important role in the development of inflammatory diseases including allergy, heart disease, diabetes and cancer. Nanomaterial-mediated antioxidant therapy is regarded as a promising strategy to treat oxidative stress-mediated inflammation. Herein, defective Ag–In–S/ZnS quantum dots (AIS/ZnS QDs) with oxygen-derived radical-scavenging capabilities are developed. Owing to their intrinsic defects and abundant surface functional groups, these quantum dots exhibit excellent oxygen-derived free radical removal efficiency in vitro . In macrophages, AIS/ZnS QDs can eliminate intracellular excessive ROS stimulated by either H2 O2 or lipopolysaccharide (LPS), thus can effectively protect macrophages against ROS-induced oxidative injury. Moreover, in the model of LPS-triggered macrophage inflammation, they exhibit benign anti-inflammatory ability by inhibiting the expression of related proinflammatory cytokines ( e.g., TNF-α and IL-6). These findings indicate that AIS/ZnS QDs hold great potential for the treatment of ROS-related inflammatory disorders.